Ionites application for separation of isotope and ion mixes in exchange processes with exchanger electroregeneration; The 8th Korea-Russia International Symposium on Science and Technology (KORUS 2004), June 26 - July 3, 2004, Tomsk, Russia; Vol. 2 - Dorofeeva (Dorofeyeva) L. I. Liudmila Ivanovna (2004, 2004)
Title screen